Functional hamstrings: quadriceps ratios in elite women's soccer players - Jenkins, N. D. M.; Hawkey, M. J.; Costa, P. B.; Fiddler, R. E.; Thompson, B. J.; Ryan, E. D.; Smith, D.; Sobolewski, E. J.; Conchola, E. C.; Akehi, K.; Cramer, J. T. (Journal of Sports Sciences, 2013)
We compared starters and non-starters for various isokinetic strength variables in elite women`s soccer players. A convenience sample of 10 starters (mean ± s; age = 20 ± 2 years; height = 170 ± 4 cm; body mass = 65 ± 5 kg) and 7 non-starters (age = 20 ± 1 years; height = 164 ± 3 cm; body mass = 63 ± 4 kg) performed maximal voluntary muscle actions of the leg extensors (concentric) and flexors (eccentric) on an isokinetic dynamometer in order to measure concentric peak torque for the leg extensors, eccentric peak torque for the leg flexors, and the functional hamstrings:quadriceps (H:Q) ratio at 1.047 rad · s-1 and 4.189 rad · s-1 concentric peak torque for the leg extensors was not different between starters and non-starters. However, it was greater at 1.047 rad · s-1 than at 4.189 rad · s-1 in both groups. Eccentric peak torque for the leg flexors was greater for the starters versus non-starters at 4.189 rad · s-1. Eccentric strength of the leg flexors at fast movement velocities may be used as an effective physiological profile and may discriminate between playing status in elite women`s soccer players.